2004
DOI: 10.1016/s0002-9440(10)63161-6
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Biopolymer Prevents Mucositis Induced by 5-Fluorouracil in Hamsters

Abstract: Oral mucositis is a common, treatment-limiting, and costly side effect of cancer treatments whose biological underpinnings remain poorly understood. In this study, mucositis induced in hamsters by 5-fluorouracil (5-FU) was observed after cheek-pouch scarifications, with and without administration of RGTA (RG1503), a polymer engineered to mimic the protective effects of heparan sulfate. RG1503 had no effects on 5-FU-induced decreases in body weight, blood cell counts, or cheek-pouch and jejunum epithelium proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…RGTAs have been shown to modulate collagen synthesis in several cell culture and tissue explant models, as well as affect the enzymatic activities of various proteases involved in extracellular matrix remodeling. 12,23,24 Briefly, RGTA facilitates the healing of injured corneas via a reduction of proteolytic, oxidative, and nitrosative damage. 25 In the literature, in vivo and in vitro experimental models concluded that various RGTAs significantly improved the speed and quality of wound repair in different tissues such as skin and also decreased woundrelated pain.…”
Section: Discussionmentioning
confidence: 99%
“…RGTAs have been shown to modulate collagen synthesis in several cell culture and tissue explant models, as well as affect the enzymatic activities of various proteases involved in extracellular matrix remodeling. 12,23,24 Briefly, RGTA facilitates the healing of injured corneas via a reduction of proteolytic, oxidative, and nitrosative damage. 25 In the literature, in vivo and in vitro experimental models concluded that various RGTAs significantly improved the speed and quality of wound repair in different tissues such as skin and also decreased woundrelated pain.…”
Section: Discussionmentioning
confidence: 99%
“…11,[15][16][17] RGTAs are characterized by their capacity to surrogate natural GAGs destroyed by glycanase activities during stress. As expected, the GAG-mimetic decreased lipid peroxidation of cell membranes and restored the activity of aconitase close to control level (Figure 1) indicating that, at low concentrations, L929 were used for their sensitivity to TNF-a mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Therefore they were also named RGTA s for ReGeneraTing Agents. Here, we postulate that GAG-mimetics can participate to regulation of apoptosis in a mechanism implicating cathepsins activation and lysosomal membrane permeabilization.…”
mentioning
confidence: 99%
“…[20][21][22][23][24] In this model, mucositis was induced by scraping the oral mucosa after bone marrow suppression was induced by massive 5-FU administration. Therefore, it has been reported that the leukocyte count after 5-FU administration decreased.…”
Section: Discussionmentioning
confidence: 99%